Strongly polarized light from highly aligned electrospun luminescent natural rubber fibers - Faita, Fabrício L. (2022)
We report the production of luminescent natural rubber micro/nanofibers with high polarized photoemission. The electrospinning technique was used to produce aligned mats from natural rubber. The fibers have diameters that vary between 200 nm and 2.5 μm and with a mean diameter size around 820 nm. The produced fibers were parallel aligned, presenting optical transparency and pronounced birefringence due to polymeric chain alignment. Luminescent elastomeric fibers were produced using a benzothiadiazole-based organic luminescent small molecule dispersed in the natural rubber precursor solution before electrospinning. The photoluminescence spectrum of the fibers indicates that the vibrational resolution is higher than for this luminescent molecule in solution and membrane. This observation was attributed to the molecular packing inside the anisotropic fiber structure, which reduces the degrees of freedom and the molecular interactions of the dye. Therefore, resulting in pronounced linear polarized emission, which could still be improved by stretching along the fiber longitudinal direction, where a dichroic ratio of 13.0 and anisotropy factor of 0.98 were obtained. The experimental observations were supported by theoretical modelling. Such a system offers great potential for technological applications like optical sensors to monitor changes in the emission degree of polarized light when exposed to different ambient conditions.